An Analysis of Millennial Farmers’ Communication Networks on Hydroponic Vegetable Marketing Topics Via Whatsapp Application (Hydroponic Farmers in Situbondo) - Sandis Wahyu Prasetiyo; Edi Dwi Cahyono; Reza Safitri (HABITAT, 2021)
The large-scale social restrictions during the COVID-19 pandemic have hampered the communication process for millennial hydroponic farmers in Situbondo. The farmers could not have their regular offline meetings. As such, they started to switch to the Whatsapp messaging application to communicate. However, the switch was done without prior need analysis, so there was no guarantee of whether the application could meet their need to communicate. This study aimed to analyze the interpersonal communication network, WA media gratification, and the relationship between the two. The communication network method was used in this study by interviewing 108 respondents through a nominalist approach and positional strategy, small group sampling followed by intact sampling. Data were analyzed using the Communication Network Analysis program UCINET Version 6.0, descriptive analysis, and analysis of variable relationships using the SPSS Version 21. The results showed that the whole network consisted of actors from various professions and backgrounds from Situbondo and outside Situbondo. The communication network structure formed a wheel with the dominance centrality degree, closeness, betweenness, and eigenvector actors by three hydroponic farmers with codes 41, 47, and 105. The level of WA media gratification, included the use and satisfaction obtained by hydroponic farmers, was very high on information, socialization, and social support. The relationship between interpersonal communication networks and WA media gratification showed a significant and very significant relationship for socialization and social support.